2012
DOI: 10.5489/cuaj.11163
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of renal cyclooxygenase expression due to partial unilateral ureteral obstruction in neonatal

Abstract: E150Cite as: Can Urol Assoc J 2013;7:E150-E155. http://dx.doi.org/10.5489/cuaj.11163. Epub 2012 March 2. AbstractIntroduction: Impaired renal water handling in response to neonatally-induced partial unilateral ureteral obstruction (PUUO) may be associated with altered expression of cyclooxygenase (COX). The purpose of the present study was to examine whether long-term PUUO induced at birth was associated with changes of COX-2. Methods: Rats were subjected to PUUO (n = 14) or a sham operation (n = 12) within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[ 21 ] While acute short-term unilateral obstruction in rats has not changed the permeability to water and reabsorptive capacity of terminal collecting duct, prolonged unilateral obstruction has resulted in increased cyclooxygenase and decreased permeability to water and urinary sodium excretion in obstructed kidney. [ 22 23 ] Since we calculated GFR based on Schwarz formula and selected unilateral obstruction, comparing GFRs in 2 kidneys (obstructed and nonobstructed) was unfeasible. However, we demonstrated that GFR after 72 h of releasing the obstruction increased significantly comparing with the previous stages.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] While acute short-term unilateral obstruction in rats has not changed the permeability to water and reabsorptive capacity of terminal collecting duct, prolonged unilateral obstruction has resulted in increased cyclooxygenase and decreased permeability to water and urinary sodium excretion in obstructed kidney. [ 22 23 ] Since we calculated GFR based on Schwarz formula and selected unilateral obstruction, comparing GFRs in 2 kidneys (obstructed and nonobstructed) was unfeasible. However, we demonstrated that GFR after 72 h of releasing the obstruction increased significantly comparing with the previous stages.…”
Section: Discussionmentioning
confidence: 99%